A Multidisciplinary Attempt at Understanding the Violence in Mexico - Rábade, José M.; García, Francisco García (International Journal of Criminology and Sociology, 2015)
Mexico has been living with a level of violence that was unimaginable only a short time ago. Why and how has Mexico arrived at this dramatic increase in violence? The goal of this study is to reflect on this question through several disciplines. The idea is to collect and contrast sufficient information from the most varied fields of knowledge, including culture and art, as well as social sciences. This is done with the ambition that all these factors will help us to understand the reasons for this terrible and complex Mexican reality.